2015
DOI: 10.4103/2231-4040.150364
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipase and inflammatory mediators by Chlorella lipid extracts for antiacne treatment

Abstract: Acne vulgaris is a chronic inflammatory disease, and its treatment is challenging due to the multifactorial etiology and emergence of antibiotic-resistant Propionibacterium acnes strains. This study was focused to reduce antibiotics usage and find an alternate therapeutic source for treating acne. Lipid extracts of six Chlorella species were tested for inhibition of lipase, reactive oxygen species (ROS) production, cytokine production using P. acnes (Microbial Type Culture Collection 1951). Lipase inhibitory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Data showed that Chlorella promotes inhibitory effects over P. acnes through attenuation of lipase activity. Also, Chlorella extracts modulated oxidative and inflammatory responses from human peripheral blood mononuclear cells stimulated by heat-killed P. acnes [19]. Sun et al (2014) proposed the use of selenium-enriched C. vulgaris cultures as means to induce bioaccumulation, producing antioxidant-rich biomass with applications in agriculture and human diet.…”
Section: Dietary Use and Effects Of Chlorella On Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Data showed that Chlorella promotes inhibitory effects over P. acnes through attenuation of lipase activity. Also, Chlorella extracts modulated oxidative and inflammatory responses from human peripheral blood mononuclear cells stimulated by heat-killed P. acnes [19]. Sun et al (2014) proposed the use of selenium-enriched C. vulgaris cultures as means to induce bioaccumulation, producing antioxidant-rich biomass with applications in agriculture and human diet.…”
Section: Dietary Use and Effects Of Chlorella On Healthmentioning
confidence: 99%
“…Also, analysis of fatty acid composition obtained from C. vulgaris indicates that, among the 19 different fatty acids found, 5 were saturated and 14 were C14 to C24 unsaturated fatty acids [19]. Bewicke and Potter (1993), in a book entitled "Chlorella: The Emerald Food", highlight the beneficial possibilities of including Chlorella in the western diets, these are: high growth rate, high protein content, resistance to climatic variations, high nutritive value and digestibility, palatability, economical production and others [20].…”
Section: Chlorella Is Rich In Polyunsaturated Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several compounds or extracts inhibiting P. acnes lipase have been identified, including extracts of green algae ( Chlorella ) and of the plant Terminalia chebula , polyhydroxylated fullerene , and vitamins B 2 , B 5 , K 3 , and K 5 . However, the molecular mechanisms involved remain unclear.…”
mentioning
confidence: 99%